Ageing and the pathogenesis of osteoarthritis - Loeser, Richard F. (Nat Rev Rheumatol, 2016)
Ageing-associated changes that affect articular tissues promote the development of osteoarthritis (OA). Although ageing and OA are closely linked, they are independent processes. Several potential mechanisms by which ageing contributes to OA have been elucidated. This Review focuses on the contributions of the following factors: age-related inflammation (also referred to as ‘inflammaging’); cellular senescence (including the senescence-associated secretory phenotype (SASP)); mitochondrial dysfunction and oxidative stress; dysfunction in energy metabolism due to reduced activity of 5′-AMP-activated protein kinase (AMPK), which is associated with reduced autophagy; and alterations in cell signalling due to age-related changes in the extracellular matrix. These various processes contribute to the development of OA by promoting a proinflammatory, catabolic state accompanied by increased susceptibility to cell death that together lead to increased joint tissue destruction and defective repair of damaged matrix. The majority of studies to date have focused on articular cartilage, and it will be important to determine whether similar mechanisms occur in other joint tissues. Improved understanding of ageing-related mechanisms that promote OA could lead to the discovery of new targets for therapies that aim to slow or stop the progression of this chronic and disabling condition.